Prevention of exacerbation in patients with moderate-to-very severe COPD with the intent to modulate respiratory microbiome: a pilot prospective, multi-center, randomized controlled trial - Hua, Jian-lan; Yang, Zi-feng; Cheng, Qi-jian; Han, Yao-pin; Li, Zheng-tu; Dai, Ran-ran; He, Bin-feng; Wu, Yi-xing; Zhang, Jing (Frontiers in Medicine, 2024)
Introduction Considering the role of bacteria in the onset of acute exacerbation of COPD (AECOPD), we hypothesized that the use of influenza-Streptococcus pneumoniae vaccination, oral probiotics or inhaled amikacin could prevent AECOPD. Methods In this pilot prospective, muti-central, randomized trial, moderate-to-very severe COPD subjects with a history of moderate-to-severe exacerbations in the previous year were enrolled and assigned in a ratio of 1:1:1:1 into 4 groups. All participants were managed based on the conventional treatment recommended by GOLD 2019 report for 3 months, with three groups receiving additional treatment of inhaled amikacin (0.4 g twice daily, 5–7 days monthly for 3 months), oral probiotic Lactobacillus rhamnosus GG (1 tablet daily for 3 months), or influenza-S. pneumoniae vaccination. The primary endpoint was time to the next onset of moderate-to-severe AECOPD from enrollment. Secondary endpoints included CAT score, mMRC score, adverse events, and survival in 12 months. Results Among all 112 analyzed subjects (101 males, 96 smokers or ex-smokers, mean ± SD age 67.19 ± 7.39 years, FEV1 41.06 ± 16.09% predicted), those who were given dual vaccination (239.7 vs. 198.2 days, p = 0.044, 95%CI [0.85, 82.13]) and oral probiotics (248.8 vs. 198.2 days, p = 0.017, 95%CI [7.49, 93.59]) had significantly delayed onset of next moderate-to-severe AECOPD than those received conventional treatment only. For subjects with high symptom burden, the exacerbations were significantly delayed in inhaled amikacin group as compared to the conventional treatment group (237.3 vs. 179.1 days, p = 0.009, 95%CI [12.40,104.04]). The three interventions seemed to be safe and well tolerated for patient with stable COPD. Conclusion The influenza-S. pneumoniae vaccine and long-term oral probiotic LGG can significantly delay the next moderate-to-severe AECOPD. Periodically amikacin inhalation seems to work in symptomatic patients. The findings in the current study warrants validation in future studies with microbiome investigation. Clinical trial registration:https://clinicaltrials.gov/, identifier NCT03449459.